2017
DOI: 10.1016/j.jsat.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of the Medication Adherence Questionnaire (MAQ) in an alcohol pharmacotherapy trial

Abstract: Background Medication nonadherence is a ubiquitous problem in pharmacology treatment for alcohol use disorders. Unintentional and purposeful nonadherence as measured by the Medication Adherence Questionnaire (MAQ) has been shown to predict problems with medication adherence; however, feedback from the MAQ has never been incorporated into a behavioral intervention to facilitate medication adherence. We assessed the integration of the MAQ into Medical Management (MM), a counseling approach frequently employed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…These findings differ somewhat from the results of a recent meta-analysis of smoking cessation trials that indicated a sustained benefit of varenicline (vs. placebo) through 12 months, but a decline in quit rates across both groups over time (Rosen et al, 2018). The sustained effects in the current study may also indicate a longitudinal benefit of behavioral counseling since all participants received 12 weeks of medical management for alcohol use (Zweben et al, 2017), a behavioral intervention adapted from the COMBINE study (Anton et al, 2006;Pettinati et al, 2005). Other studies indicate that behavioral treatments for substance use can produce lasting benefits beyond the end of treatment (e.g., (Carroll et al, 1994;O'Malley et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings differ somewhat from the results of a recent meta-analysis of smoking cessation trials that indicated a sustained benefit of varenicline (vs. placebo) through 12 months, but a decline in quit rates across both groups over time (Rosen et al, 2018). The sustained effects in the current study may also indicate a longitudinal benefit of behavioral counseling since all participants received 12 weeks of medical management for alcohol use (Zweben et al, 2017), a behavioral intervention adapted from the COMBINE study (Anton et al, 2006;Pettinati et al, 2005). Other studies indicate that behavioral treatments for substance use can produce lasting benefits beyond the end of treatment (e.g., (Carroll et al, 1994;O'Malley et al, 1996).…”
Section: Discussioncontrasting
confidence: 99%
“…After week 16, use of medication was tapered over 2 weeks (0.5 mg twice daily and then 0.5 mg daily). Participants also received 12 brief counseling sessions with a healthcare professional for medical management (MM) (Zweben et al, 2017) adapted from the COMBINE study (Anton et al, 2006;Pettinati et al, 2005). The first 4 weeks of treatment focused on medication adherence and stabilization on medication.…”
Section: Study Objectives and Designmentioning
confidence: 99%
“…Following randomization, participants attended 12 treatment research sessions (weeks 1, 2, 3, 4, 5, 6, 7, 9, 11, 13, 15, and 17) and met with a medical professional for MM adapted from the COMBINE study . The first 4 sessions addressed tolerability and supported medication adherence; the remaining sessions addressed finalizing drinking goals as well as developing and implementing strategies for changing drinking.…”
Section: Methodsmentioning
confidence: 99%